Population dynamics and growth of perch in a small, humic lake over a 20-year period : importance of abiotic and biotic factors - Rask, Martti; Sairanen, Samuli; Vesala, Sami; Arvola, Lauri; Estlander, Satu; Olin, Mikko
2015